In Defense of Intellectual Autonomy: A Response to Hendricks. (August 2014) - Moyo, Sam; Jha, Praveen; Yeros, Paris
This article is a response to Fred Hendricks' critique of our most recent statement on the classical and contemporary agrarian questions. The critique, we believe, is a gross misunderstanding of our position on a variety of issues, including populism, nationalism, the character of the peasantry and industrialization. In defence of our intellectual integrity and autonomy, we restate here our basic positions and outline the trajectory of our collective research projects, in the hope that our positions are put into better perspective.